2023
DOI: 10.1038/s41557-023-01157-6
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free reduction of CO2 to formate using a photochemical organohydride-catalyst recycling strategy

Abstract: The increasing CO2 concentration in the atmosphere is an urgent social problem that has to be resolved. Reducing CO2 into compounds useful as energy sources and carbon materials is desirable. For the CO2 reduction reaction (CO2RR) to be operational on a global scale, the catalyst system must: (1) use only renewable energy, (2) be built from abundantly available elements, and (3) not require highenergy reactants. Although light is an alluring energy source, most existing methods utilize electricity. Furthermore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…Based on the experimental results and knowledge obtained from the literature, 24 a reaction mechanism is proposed (Figure 6). BI + -Ph-NMe 2 is excited with visible light to obtain BI + -Ph-NMe 2 *.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the experimental results and knowledge obtained from the literature, 24 a reaction mechanism is proposed (Figure 6). BI + -Ph-NMe 2 is excited with visible light to obtain BI + -Ph-NMe 2 *.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The mass balances (sum of the yields of BI + -Ar and recovered BIH-Ar ) were 67 and 100% for BIH-1Nap-OH and BIH-Ph-NMe 2 , respectively, indicating that BI + -Ph-NMe 2 / BIH-Ph-NMe 2 can constitute a robust organohydride-recycling photocatalytic system. As suggested in a previous study, the observed moderate yield (54%) of BIH-Ph-NMe 2 in the photochemical regeneration of organohydrides is not problematic for future application as a catalyst . Control experiments suggested that light irradiation, a base, and ascorbic acid were indispensable for this reaction (entries 10–12).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of the redox chemistry of benzimidazolines (BIH–R), which are artificial analogues of the reduced form of nicotinamide adenine dinucleotide (NADH), began more than three decades ago, and the applications of these substances in various chemical fields have been probed in detail. ,,,,, In contrast, investigations of the redox chemistry of their oxidized forms, benzimidazoliums (BI + –R), are extremely limited. , In addition, it is not common for cationic photocatalysts to be utilized to promote reduction reactions. , Therefore, the investigation described in this manuscript introduces a new aspect of BI + –R chemistry. As described above, among the subjects of future investigation includes more exploration of the influence of the para -substituent of the −PhNAr 2 moiety as well as solvent effects on the catalytic mechanism of 1 .…”
Section: Discussionmentioning
confidence: 99%